The campus effect: built environment, physical activity and active transportation behaviors of the Kansas State University students, faculty, and staff in 2008 and 2016 - Gilmore, Katelyn Erin Opal (Kansas State University, 2018)
Introduction: Transportation-related physical activity can help adults can meet moderate physical activity guidelines. Only 52% of United States adults meet the physical activity guidelines on a regular basis. Active transportation (AT) is a healthier alternative to motorized transport and incorporates more physical activity into one’s day. Universities with supportive built environment features, such as pedestrian and bicycling infrastructure and amenities, can support AT choices. This study was conducted to (1) examine differences in the overall physical activity and AT behaviors of university students, faculty and staff in 2008 and 2016; and (2) explore influential factors for transportation choice and perceptions of the campus built environment in 2016. Physical activity and AT behaviors were hypothesized to be greater in 2016 than 2008 due to changes in supportive built environment features on campus. Methods: All students, faculty and staff members at Kansas State University’s Manhattan campus were eligible to participate in this repeated cross-sectional study by completing a survey in 2008 and 2016. Similar survey questions were asked both years to allow for comparisons. Questions asked about physical activity levels, transportation modes, factors influencing mode choice, and (in 2016) written feedback regarding built environment changes on campus and additional changes needed. After dichotomizing responses by role (students or faculty/staff), independent samples t-tests were used to assess differences in physical activity and transportation modes between survey years. The most influential reasons for transportation mode in 2016 were identified and compared by role. Multiple linear regression models were used to predict variance within each transportation mode. Themes were identified within the written feedback. Results: In spring 2016, 1006 participants (815 students, 80 faculty, and 111 staff members) completed the survey. This compared to 800 participants in spring 2008 (368 students, 256 faculty, and 176 staff members). There was a significant difference for greater moderate but not vigorous physical activity for both students and faculty/staff in 2016 than 2008. Days per week of driving, biking, and other transportation were significantly greater for students, while driving, walking, and biking were significantly greater for faculty/staff in 2016 than 2008. For students, linear regression predicted 21.4% of the variance for driving, 14.7% of walking, and 5.4% of biking for transport. Strongest predictors for students were: health benefits (β = -0.27) and time constraints (β = 0.21) for driving, traffic congestion (β = 0.19) and length of time frequenting campus (β = -0.17) for walking, and safety concerns for crime (β = -0.26) for biking. For faculty/staff, linear regression predicted 23.5% of the variance for driving, 70.3% of walking, 29.8% of biking, and 14.0% of other transport. Strongest predictors for faculty/staff were: time constraints (β = 0.34) and health benefits (β = -0.30) for driving, health benefits (β = 0.28) and time constraints (β = -0.55) for walking, environmental concerns (e.g., pollution; β = 0.35) and safety concerns for crime (β = -0.43) for biking, and weather (β = -0.37) for other transportation. From 436 written responses, main themes for AT influences were: construction (n = 174), parking (n = 128), walking (n = 99), and biking (n = 64). From 403 responses for suggestions for improvements on the commute to campus main themes were: bike lanes (n = 85), sidewalks (n = 29), limits of construction (n = 28), and KSU master plan (n = 26). Conclusions: Time constraints was a key factor for both students and faculty/staff that positively predicted driving and negatively predicted walking behaviors. Few campus built environment features emerged as key predictive factors. Understanding key influences for transportation-related physical activity and commuting behaviors in a university population are useful for health behavior promotion as well as campus planning. Future research should further study the relationship between mode of transportation and other health behaviors in students, faculty, and staff.
Keywords: Active Transportation; Built Environment; Physical Activity; College Health